Reduced solutions of Douglas equations and angles between subspaces - Arias, Maria Laura (2009)
In this paper we study some particular solutions of Douglas type equations by means of generalized inverses and angles. We apply this result to characterize positive solutions and some special projections which are symmetrizable for a semidefinited positive bounded linear operator.